Factors affecting the study location preferences of Bachelor of Library and Information Science students of the University of the Philippines Diliman - Geroca, Jeseliza A. (2013)
This study was conducted to determine the study location preferences of undergraduate students of the School of Library and Information Studies (SLIS) in the University of the Philippines (UP) Diliman and the factors that affect these preferences. Several factors were classified into five different categories: demographic, environmental, sociological, physiological and technological.